(3GdCQHYjf aj EeGeI GdCFeI GdWGgQjfs - (3GdTjQGRjs
(3ChdgG (B:s
(3GdMeO ddg CeG HYO aEfi deG QCjJ CaVd eG jJbQH Hg Edi Gddg QH GdYGdejf eYQaI GdCFeI GdCKfi YTQ GdCWgGQ GdeYUhejf s
(3BNQgG (B:s
(3abGe YHO Gddg Hf CHj QHjYI Hf GdeZjQI GdeNRhei afGOi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs